Perceived effect on the membership in the fraternity and sorority of the selected students of UM Bansalan campus - Natad, Eduardo L. Jr.; Montero, Patrick C.; Baliscao, Albert B. (--Davao del Sur: UM Bansalan College, 2012)
The study aims to determine the perceived effect on the membership in the fraternity and sorority of the selected students of UM Bansalan Campus in terms of personality development and academic performance. In addition, it is designed to know the Demography of the students in terms of Age, Sex, Civil Status and Course. Furthermore, this study aimed to find out the effect on the membership in the fraternity and sorority of the selected students of UM Bansalan Campus.